Sustainability of Water Availability: A Study of Tanjung Pinang, Bintan Island - Kurniawan, Hendra; Kismartini, Kismartini; Purnaweni, Hartuti (Iapa Proceedings Conference, 2024)
Water is a basic need of all living things. Since the beginning of life all living things really need water for their survival, so that water needs must be met properly. The fulfilment of water needs in Tanjungpinang City comes from Sei Pulai Reservoir and Gesek Reservoir which are fully rain-fed reservoirs. However, the condition of Sei Pulai Reservoir is damaged so that its sustainability is worrying. The damage to the condition of the reservoir is caused by various factors that are very complex until finally the water discharge has decreased. This research was conducted with the aim of describing the condition of water availability in Tanjungpinang City and analysing the urgency of management carried out by the government in meeting the needs of Water Resources in the perspective of public administration. Through a qualitative approach, the results showed that the water needs in Tanjungpinang City had only been fulfilled around 35.27%. With the increasing population in the future, the need for water will certainly also increase, requiring the government to be present to solve the problems that occur and carry out the best management in fulfilling water needs.